Peran locus of control pada pengujian model perencanaan dana pensiun karyawan sektor swasta di Surabaya - Ismawati Ismawati; Rr. Iramani (Universitas Hayam Wuruk Perbanas, 2021)
This study investigates the factors affecting retirement planning by examining therelationship between ﬁnancial literacy, locus of control, materialism, future orientation,and saving orientation. It used a questionnaire on 128 private sector employees inSurabaya and the data were analyzed using PLS. It was found that locus of control, future orientation, and saving orientation have an effect on retirement planning. Another one shows ﬁnancial literacy has an insigniﬁcant positive effect on retirement planning and external locus of control mediating the effect of ﬁnancial literacy on pension planningbehavior. Materialism has no effect on retirement planning. Future orientation has a positive effect on retirement planning and saving orientation is able to mediate the effect of future orientation on retirement planning. It can be implied that—if an individual has a better future orientation and saving orientation—the better the retirement plan he has;an individual who has high ﬁnancial literacy must be accompanied by good self-controlin order to be able to plan his retirement wisely. It can be used for a useful reference for organizations to develop retirement planning in the context of a developed city such as Surabaya.